If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -8 = 10 + -3p Reorder the terms: -8 + 8p = 10 + -3p Solving -8 + 8p = 10 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. -8 + 8p + 3p = 10 + -3p + 3p Combine like terms: 8p + 3p = 11p -8 + 11p = 10 + -3p + 3p Combine like terms: -3p + 3p = 0 -8 + 11p = 10 + 0 -8 + 11p = 10 Add '8' to each side of the equation. -8 + 8 + 11p = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 11p = 10 + 8 11p = 10 + 8 Combine like terms: 10 + 8 = 18 11p = 18 Divide each side by '11'. p = 1.636363636 Simplifying p = 1.636363636
| 5-2y=y | | 4x^2-9x+11=2x+5 | | 8x^3+24x-24x^2-8=0 | | 4x^2+24x+8=0 | | 2x^3+3x^2-12x-10=0 | | x^2+10x+39=-5x-5 | | 6k-5k+10-18= | | h^2+10h=21 | | 7t+3t=30 | | 7t+3t=11 | | 5x+39=28 | | 7.32=.05x-.18 | | 8x-1=4x+23 | | 20x+41=-199 | | 9x+40=-14 | | 13.8=x-2.4 | | y=x^2-10x-21 | | 14x+3=-25 | | 7y+4(3-y)=18 | | x^3+18*x+6=0 | | -4x-12=-36 | | (-3x-6)(7x+3)= | | 1A+2B+3C=30 | | 2(x+7)-7=9 | | 5-x=3(x-1) | | -2(x+3)=20 | | 24-10x=9 | | 5x-4y=17 | | n^4-n^3-n+1=0 | | -2x+3y=52 | | 25x=125x+2 | | 8z+9-7z-2= |